Psychosocial and Physical Rehabilitation of Burn Survivors: A large multicentre cluster randomised controlled trial from Pakistan - N. Chaudhry; M. panagioti; A. B. Khoso; T. Kiran; A. Blakemore; K. Lovell; M. M. Bashir; Z. U. Haq; M. Hashmi; Z. H. Suhag; H. Brooks; E. McIntosh; et al. (European Psychiatry, 2023)
Introduction Globally, burns are responsible for around 11 million injuries and 180 000 burn-related deaths yearly. Unfortunately, 9 of 10 burn injuries and deaths happen in low-and-middle-income countries (LMICs) such as Pakistan. One in three people admitted to hospitals with burn injuries die within three weeks, and survivors face serious lifelong physical, emotional and psychosocial problems. This may result in anxiety, depression, post-traumatic stress disorder, increased mortality and social disintegration. This study aims to evaluate if implementation of a culturally adapted multidisciplinary rehabilitation programme for burn survivors is clinically and cost-effective, sustainable and scalable across Pakistan. Objectives